Pengaruh Motivasi Kerja terhadap Kinerja Karyawan PT MItra Utama Grafika - Eigis Yani Pramularso (Widya Cipta - Jurnal Sekretari dan Manajemen, 2017)
Abstract - Superior employee performance is the key factor in the company to achieve its goals. One that can affect the performance of employees is their motivation to work. This study aims to determine the effect of work motivation on employee performance PT Mitra Utama Graphic. The number of respondents in this study were 35 employees. The data collection is done by using a questionnaire. The analysis of the data used is simple regression analysis, t-test, correlation coefficient, and the coefficient of determination. The results showed that motivation significantly influence the performance of employees of PT Mitra Utama Graphic. The magnitude of the correlation coefficient indicates the number 0,52, it means the relationship work motivation on employee performance is quite strong. The coefficient of determination or R Squared = 0,270 which means work motivation affects employee performance by 27% while the rest influenced by other factors outside the study. Keywords: work motivation, employee performance